THE EFFECT OF DEBT POLICY AND DIVIDEND POLICY ON COMPANY VALUE WITH COMPANY SIZE AS A MODERATION VARIABLE - SURYANI; RANTI MELASARI (Indragiri Research Center (ingreat), 2023)
This study aims to obtain empirical evidence and analyze the influence of debt and policy policies dividends on firm value with company size as a moderating variable (an empirical study of property and real estate companies listed on the Indonesia Stock Exchange for the 2017-2019 period). The population in this study are mining companies listed on the Indonesia Stock Exchange in 2017-2019. Selection of the sample in this study using techniques Purposive sampling, and obtained as many as 11 companies or 33 samples that can be used in this study. The analytical method used in this study is multiple linear regression, and using Metode Regression Analysis with the classical assumption test used data normality test, multicollinearity, heteroscedasticity and autocorrelation test. This research also uses a descriptive statistical test used to provide an overview of the object studied through the research sample. The results of this study indicate that debt policy has a significant effect on firm value, policy dividends do not affect firm value, firm size weakens the effect of debt policy on firm value, and firm size weakens the effect of dividend policy on firm value.